Impact of Closure of a Safety Net HIV Case Management Agency. Issue 2 (June 2015) - Khosla, Nidhi; Kennedy, Caitlin; Winch, Peter; Latkin, Carl; Marsteller, Jill
<x xml:space="preserve">Abstract</x> Safety net healthcare agencies serve important roles within organizational networks, yet little research has examined the impact of their closure on other healthcare organizations. Using a case study approach, we explored the impact of the sudden closure of a prominent safety net HIV agency on other HIV service organizations and clients in a U.S. city. We conducted 23 key informant interviews and examined newspaper articles and agency publications. The agency's closure led to many clients being lost to the system, delays in care, and the loss of a caring community asset that provided unique services together (e.g., legal aid, showers, laundry, lockers for homeless people). Other organizations suffered since they had relied on the agency for case management services. Agencies should engage in transition planning and sustainability planning to ensure continuity of services. Policymakers must implement health system changes in a planned manner wherever possible.